2015
DOI: 10.1111/tid.12434
|View full text |Cite
|
Sign up to set email alerts
|

Tenofovir/entecavir monotherapy after hepatitis B immunoglobulin withdrawal is safe and effective in the prevention of hepatitis B in liver transplant recipients

Abstract: Maintenance therapy with newer NAs, after discontinuation of HBIG prophylaxis, was safe and effective, with a low rate of serological recurrence and no evident clinical, biochemical, or virological consequences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 27 publications
3
32
0
2
Order By: Relevance
“…152 Conversely, lifelong combination therapy should be given to patients who are at a high risk for HBV recurrence, namely those who are HBV DNA positive at the time of liver transplantation, who are HBeAg-positive, have HCC, and HDV or HIV co-infection. [153][154][155] In the setting of liver transplantation, nephrotoxicity should always be considered and renal function should be carefully monitored because of the concomitant use of calcineurin inhibitors. When the immune system is therapeutically suppressed in the context of liver transplantation, there is potential for HBV reactivation in HBsAg-negative patients receiving donor organs with evidence of past HBV infection (anti-HBc positive).…”
Section: Recommendationsmentioning
confidence: 99%
“…152 Conversely, lifelong combination therapy should be given to patients who are at a high risk for HBV recurrence, namely those who are HBV DNA positive at the time of liver transplantation, who are HBeAg-positive, have HCC, and HDV or HIV co-infection. [153][154][155] In the setting of liver transplantation, nephrotoxicity should always be considered and renal function should be carefully monitored because of the concomitant use of calcineurin inhibitors. When the immune system is therapeutically suppressed in the context of liver transplantation, there is potential for HBV reactivation in HBsAg-negative patients receiving donor organs with evidence of past HBV infection (anti-HBc positive).…”
Section: Recommendationsmentioning
confidence: 99%
“…A concern with TDF use has been nephrotoxicity. This has been rare in studies on chronic hepatitis B and postliver transplant, although it has been a significant issue in some patients treated with TDF for HIV . One patient in our cohort had overt features of Fanconi's syndrome, necessitating a change of therapy to entecavir, which underlines the potential for renal toxicity with TDF therapy in the posttransplant setting.…”
Section: Discussionmentioning
confidence: 84%
“…The finding that tenofovir disoproxil fumarate (TDF) is highly active against LAM‐resistant viruses suggests that the combination of this drug with LAM may at least be as effective as traditional HBIg/LAM combination therapy. However, the need for additional LAM is questionable because no cases of tenofovir resistance have been identified in either treatment‐naïve or nucleos(t)ide‐experienced patients …”
Section: Introductionmentioning
confidence: 99%
“…Another 2 studies demonstrated a trend toward improved eGFR/CKD stage under sequential TAF treatment following TDF or HBIG+NAs 48,49 . The renal function remained at a stable level in other trials 35,36,40,41,52 .…”
Section: Renal Functionmentioning
confidence: 81%
“…≤6m vs >6m). In this regard, individualized decision should be made based on kinetics of anti-HBs 40,44,69 . We did not conduct strati cation by dosage because most of the studies applied low-dose of HBIG (≤ 1000 IU) one week/month post-LT.…”
Section: Discussionmentioning
confidence: 99%